2018
DOI: 10.1016/j.nicl.2018.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine dependence with and without psychotic symptoms: A multi-modal brain imaging study

Abstract: ObjectiveMethamphetamine dependence can lead to psychotic symptoms which may be mediated by frontal, striatal, limbic, and thalamic regions. There are few neuroimaging data that allow comparison of individuals with methamphetamine dependence who do, and do not, have psychosis. Two complementary imaging techniques were employed to investigate neurocircuitry associated with methamphetamine dependence with and without psychotic symptoms.MethodsThree groups of participants were recruited: methamphetamine dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…The results from the ALFF analysis are in line with previous findings about methamphetamine addiction and indicate that the frontal lobes and thalamus were changed, possibly due to decreased blood flow and metabolism in these areas (Hsieh et al., 2014; Vuletic et al., 2018). Deficits in frontal lobe structure have been widely reported in MA users (London, Kohno, Morales, & Ballard, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results from the ALFF analysis are in line with previous findings about methamphetamine addiction and indicate that the frontal lobes and thalamus were changed, possibly due to decreased blood flow and metabolism in these areas (Hsieh et al., 2014; Vuletic et al., 2018). Deficits in frontal lobe structure have been widely reported in MA users (London, Kohno, Morales, & Ballard, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Neuroimaging provides a reliable technical means for studying the neurobiological mechanism of MAP. In vivo human studies using positron emission tomography (PET) and arterial spin labeling (ASL) magnetic resonance imaging, researchers found changes in the parameters of glucose metabolism and cerebral perfusion in the frontal, striatal, and limbic regions of MAUD and psychotic individuals (Vuletic et al., 2018). There are, however, no resting‐state functional MRI data that reveal the neurocircuitry underling MAP.…”
Section: Introductionmentioning
confidence: 99%
“…44 It is known that methamphetamine reduces the density of dopamine and serotonin receptors, as well as D 2 receptors and vesicular monoamine transporter-2 within the brain. 45 Striatal and thalamic glucose metabolism are also altered, with some studies reporting a decrease of glucose metabolism in the anterior cingulate cortex. 45 Some areas of the brain shrink by approximately 10%, particularly in the ventromedial prefrontal cortex, orbital frontal cortex and the insula.…”
Section: Medical Usementioning
confidence: 99%
“…45 Striatal and thalamic glucose metabolism are also altered, with some studies reporting a decrease of glucose metabolism in the anterior cingulate cortex. 45 Some areas of the brain shrink by approximately 10%, particularly in the ventromedial prefrontal cortex, orbital frontal cortex and the insula. 1 Enlarged striatal volume has been recorded in some instances.…”
Section: Medical Usementioning
confidence: 99%
“…A multimodal brain imaging study observed that methamphetamine users (MAP and nonpsychotic methamphetamine user groups) demonstrated decreased glucose metabolism in the left insula, left precentral gyrus, and the anterior cingulate cortex when compared with healthy controls (Vuletic et al, ). Moreover, participants in the MAP group demonstrated decreased glucose metabolism in the left precentral gyrus and left inferior frontal gyrus and both increased glucose metabolism and cerebral perfusion in the putamen and pallidum.…”
Section: Biological Basis Of Mapmentioning
confidence: 99%